2015
DOI: 10.1038/ismej.2015.146
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal variation selects for diet–microbe co-metabolic traits in the gut of Gorilla spp

Abstract: Although the critical role that our gastrointestinal microbes play in host physiology is now well established, we know little about the factors that influenced the evolution of primate gut microbiomes. To further understand current gut microbiome configurations and diet-microbe co-metabolic fingerprints in primates, from an evolutionary perspective, we characterized fecal bacterial communities and metabolomic profiles in 228 fecal samples of lowland and mountain gorillas (G. g. gorilla and G. b. beringei, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
108
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 71 publications
14
108
1
Order By: Relevance
“…Microbiome composition can fluctuate in response to dietary and environmental changes. Seasonal availability of food and modifications to the diet of individuals have been shown to influence microbiome composition in several mammalian species (Amato et al, 2014;Davenport et al, 2014;Degnan et al, 2012;Gomez et al, 2016;Kohl & Dearing, 2014;Sun et al, 2016;Turnbaugh et al, 2009). In humans, adopting a high-protein diet increases the abundance of bile-tolerant bacteria, whereas a plant-based diet enriches microbial taxa that specialize in carbohydrate fermentation (David et al, 2014;O'Keefe et al, 2015), paralleling the differences observed in gut microbiomes of hunter-gathers vs. humans in industrialized societies (Morton et al, 2015;Rampelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome composition can fluctuate in response to dietary and environmental changes. Seasonal availability of food and modifications to the diet of individuals have been shown to influence microbiome composition in several mammalian species (Amato et al, 2014;Davenport et al, 2014;Degnan et al, 2012;Gomez et al, 2016;Kohl & Dearing, 2014;Sun et al, 2016;Turnbaugh et al, 2009). In humans, adopting a high-protein diet increases the abundance of bile-tolerant bacteria, whereas a plant-based diet enriches microbial taxa that specialize in carbohydrate fermentation (David et al, 2014;O'Keefe et al, 2015), paralleling the differences observed in gut microbiomes of hunter-gathers vs. humans in industrialized societies (Morton et al, 2015;Rampelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, Prevotella increased markedly during months characterized by fruit consumption, similar to what has been found in western lowland gorillas (Gomez et al. 2016). In ruminants, Prevotella digest noncellulosic polysaccharides and pectin (White, Lamed, Bayer, & Flint, 2014), and in humans, high levels of Prevotella have been associated with a carbohydrate‐ and sugar‐rich diet (Wu et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, western lowland gorillas ( Gorilla gorilla ) display an increase in the abundance of microbes involved in fiber breakdown in response to low fruit availability (Gomez et al. 2016). In black howler monkeys ( Alouatta pigra ), an increase in the abundance of Ruminococcaceae, which are efficient fermenters of nonsoluble carbohydrates, was noted during periods of reduced energy intake and might be a mechanism to compensate for low food quality (Amato et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of NHPs uncovered part of their hidden microbial diversity but only very partially contributed to the extension of the genetic blueprint of the microbiome in these hosts. Several 16S rRNA gene amplicon sequencing studies investigated the microbiome composition of NHPs [24][25][26][27][28][29][30][31][32], and some, including a meta-analysis [33], investigated the overlap and specificity of microbial communities associated with humans and NHPs [34][35][36]. Yet, because this approach has a limited phylogenetic resolution and lacks functional characterization, many co-diversification aspects cannot be studied.…”
Section: Introductionmentioning
confidence: 99%